2008
DOI: 10.1111/j.1469-0691.2007.01926.x
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of IgG antibodies against Bordetella pertussis in healthy individuals aged 4–24 years in Turkey

Abstract: The distribution of IgG antibodies to Bordetella pertussis was investigated in serum samples from 550 subjects, aged 4-24 years, to determine the optimal age for booster immunisation. Levels of antibody to B. pertussis antigens were determined using an ELISA that measures a mixture of pertussis toxin, filamentous haemagglutinin and lipopolysaccharide. Geometric mean titres of anti-pertussis antibodies in subjects aged 4-6 years were significantly lower than those in other age groups, which reflects waning immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
1
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 10 publications
2
12
1
4
Order By: Relevance
“…Although many studies have explained the seroprevalence of pertussis in industrialized countries, only few studies have reported its incidence in developing countries. This study showed that vaccine-induced immunity decreases by ages of 6-7 years, which was similar to the finding of several studies in the Middle East (4,11,12).…”
Section: Discussionsupporting
confidence: 91%
“…Although many studies have explained the seroprevalence of pertussis in industrialized countries, only few studies have reported its incidence in developing countries. This study showed that vaccine-induced immunity decreases by ages of 6-7 years, which was similar to the finding of several studies in the Middle East (4,11,12).…”
Section: Discussionsupporting
confidence: 91%
“…This type of increasing sero-prevalence with age has been observed with good immunization coverage during childhood [27]. A study conducted in Turkey, where the final dose of whole cell pertussis vaccine is given at the age of 18 months, the pertussis antibodies were highest at 51.4 U/mL in the 13 to 18 years age group similar to findings from this study [23]. In contrast, a study done in Nashville, where the last vaccine dose is given at the age of 4 to 6 years, two peaks of antibody titres were noted, one at the age range of 4 to 6 years while the other at 13 to 17 years [28].…”
Section: Discussionsupporting
confidence: 86%
“…The median anti PT IgG level was lowest in the 8 to 11 year age group. Several other studies done to determine the sero-prevalence of pertussis has shown similar findings [23]. A study done in the Czech Republic to determine levels of the anti-PT antibodies after childhood vaccination showed that seropositivity in children declines rapidly after the last dose of vaccination and the lowest level of anti PT antibodies were observed among preschool age group [24].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Gender did not influence the seroimmunity in our study; the same was reported by several other investigators. [23][24][25][26] In the current study, serum pertussis IgG titres increased with age among the infants' group being lowest below 6 months of age and higher in the 12 to 24 months old which is expected due to the receival of booster doses of the vaccine. A relevant study showed that pertussis antibody levels >30 U/ml were observed with higher frequency in infants younger than 2 years of age who completed the vaccination schedule .…”
Section: Discussionmentioning
confidence: 53%